Secondary forest succession buffers extreme temperature impacts on subtropical Asian ants. Issue 4 (25th August 2021) - Lee, Roger Ho; Morgan, Brett; Liu, Cong; Fellowes, John R.; Guénard, Benoit
Abstract: Secondary forest succession may restore microclimatic refugia for ectotherms and play a fundamental role in mitigating the combined effects of deforestation and climate warming on biodiversity; however, empirical evidence remains limited by short‐term, coarse‐scale, and solely taxonomic‐based approaches. We hypothesize that ant assemblage composition will respond differently to an increased frequency of extreme heat events between sites with and without microclimatic refugia provided by secondary forest's regrowth. We test this hypothesis by integrating comprehensive historic surveys (1992–1994) and contemporary resampling (2015–2017) of ant assemblages to investigate how soil surface temperatures (estimated by microclimatic models [30 × 30 m]) and physical parameters (e.g., canopy cover) over the past >20 yr drive changes in their taxonomic, functional, and phylogenetic diversity for open (grasslands and shrublands) and closed (secondary forests) habitat types. Our results show a significant spatial turnover in the ant assemblage composition in both habitat types over the past two decades. Furthermore, for taxonomic, functional and phylogenetic spatial beta diversity, temperature became the primary variable explaining the differences in species composition among sites in open habitats, but not in closed habitats. Nevertheless, leaf litter cover may, to a certain extent, provide some thermal buffer for litter‐dwelling species exposed to extreme heat. On the contrary, within forests, canopy cover mitigated the adverse impact of extreme heat on ant assemblages, with a shift toward smaller body size observed over time only in sites with lower canopy cover. These findings highlight the importance of restored canopy in providing thermal buffering for understory ectotherms. While tropical forest restoration represents an essential component in enhancing species resilience under climate warming, additionally we considered that the restoration of microclimatic regimes across different land use types is essential to conserve tropical biodiversity across the deforested landscape.